Effect of Giving Galoba (Hornstedtia alliacea) Fruit Extract on Catalase Activity in Mice (Mus musculus) Hyperglycemia Induced by MultipleLow Dose-Streptozotocin (MLD-STZ) - Elisa Melinia Perangin-angin; Rachmawati Dwi Agustin; Indrawanti Kusadhiani (MEDULA: Jurnal Ilmiah Fakultas Kedokteran Universitas Halu Oleo, 2024)
ABSTRACT Background: Hyperglycemia is a medical condition in which the fasting blood sugar level is ≥100 mg/dL. Prolonged hyperglycemia causes pancreatic β-cells to malfunction and causes a decrease in insulin secretion. Diabetes mellitus is a metabolic disease characterized by chronic hyperglycemia which occurs when there is an increase in blood glucose levels due to the pancreas not producing enough insulin or the body not using insulin effectively or a combination of both. Galoba fruit (Hornstedtia alliacea) is a plant endemic to Maluku that contains antioxidant compounds which are thought to increase catalase enzyme activity after hyperglycemia. Purpose(s): This study aimed to determine the effect of giving Galoba fruit extract (Hornstedtia alliacea) on the activity of the catalase enzyme in serum mice (Mus musculus) with MLD-streptozotocin induced (Multiple Low Dose Streptozotocin) hyperglycemia. Methods: This research was an experimental study with a post-test only group design. Twenty-four mice were divided into six treatment groups: normal control (KN), negative control (K-), positive control (K+), 100% concentration of Galoba fruit extract (P1), 75% concentration of Galoba fruit extract (P2), and Galoba fruit concentration was 50% (P3). Groups P1, P2, and P3 were induced using streptozotocin at a dose of 40 mg/kg BW in hyperglycemic mice and given an extract at a dose of 0.2 mL according to the concentration of each Galoba fruit. Group K+ was induced by streptozotocin and given metformin therapy at a dose of 0.2 mL. Induction of MLD-streptozotocin at a dose of 40 mg/kg for 5 consecutive days in a row. Administration of therapy in groups of K+, P1, P2, and P3 for 21 days. After the end of treatment, blood serum was taken from the heart to measure the activity of the catalase enzyme. Results: Galoba fruit extract (Hornstedtia alliacea) increased the catalase activity, but it was not significant effect on increasing the activity of the catalase enzyme (p> 0.05). The group of mice that experienced the greatest increase in enzyme activity came from the P3 group at 0.6716 U/mL (61%), followed by P2 at 0.6119 U/mL (57%), and P1 at 0.3435 U/mL (25%). Conclusion: The increased activity of the catalase enzyme was due to the presence of secondary metabolites of flavonoids and terpenoids from the results of phytochemical tests contained in Galoba fruit (Hornstedtia alliacea). Keywords: Catalase Enzyme ; Hornstedtia alliacea; Hyperglycemia